Determination of the gross activity of uranium, plutonium, americium and strontium in environmental samples using solid-state scintillation - Janda, Jiří; Tichá, Jitka (Journal of environmental radioactivity, 2018)
Rapid determination of selected gross alpha and beta emitters in environmental matrices by solid-state scintillation technique is discussed. This method is based on sample treatment using microwave reactor and direct measurement of digested products using powder scintillator and alkaline solution as a substitute for traditional liquid scintillation cocktail. The selected group of radionuclides was chosen with respect to their use in nuclear industry, high radiotoxicity, and the possibility of potential misuse. The work aimed at verifying the connection of microwave decomposition using alkaline solution with solid-state scintillation using a powder scintillator YAP:Ce together with an alkaline medium.
Keywords: scintilace - počítání; Scintillation Counting; Plutonium; Uranium; Radiation Monitoring; Rapid determination; YAP:Ce; Radioactive Pollutants; Americium; radioaktivní znečišťující látky; Microwave digestion; plutonium; Solid-state scintillation; americium; monitorování radiace; Strontium Radioisotopes; radioizotopy stroncia; uran